COVID-19 Prophylaxis Efforts Based on Natural Antiviral Plant Extracts and Their Compounds - Sytar, Oksana; Brestic, Marian; Hajihashemi, Shokoofeh; Skalicky, Milan; Kubeš, Jan; Lamilla-Tamayo, Laura; Ibrahimova, Ulkar; Ibadullayeva, Sayyara; Landi, Marco (Molecules (Basel, Switzerland), 2021)
During the time of the novel coronavirus disease 2019 (COVID-19) pandemic, it has been crucial to search for novel antiviral drugs from plants and well as other natural sources as alternatives for prophylaxis. This work reviews the antiviral potential of plant extracts, and the results of previous research for the treatment and prophylaxis of coronavirus disease and previous kinds of representative coronaviruses group. Detailed descriptions of medicinal herbs and crops based on their origin native area, plant parts used, and their antiviral potentials have been conducted. The possible role of plant-derived natural antiviral compounds for the development of plant-based drugs against coronavirus has been described. To identify useful scientific trends, VOSviewer visualization of presented scientific data analysis was used.
Keywords: léčivé rostliny; Data Visualization; vizualizace dat; alkaloidy; Terpenes; plant chemo-diversity; coronaviruses group; COVID-19; antivirové látky; Alkaloids; rostlinné extrakty; Plants, Medicinal; biological active compounds; flavonoidy; terpeny; Flavonoids; Humans; COVID-19 Drug Treatment; Plant Extracts; farmakoterapie COVID-19; Antiviral Agents; lidé